Peran Teologi Paulus dalam Roma 9-11 bagi Identitas Kristen di Tengah Realitas Israel Modern - Bangun, Grace Yunita Apulina (STT Pelita Dunia, 2025)
This study aims to analyze Pauline theology in Romans 9–11 as a foundation for forming a responsible Christian identity amidst the reality of modern Israel. The research employs a qualitative method through literature study, exegetical-theological analysis, and a contextual theological approach. The results indicate that Paul rejects two extremes: Supersessionism, which negates the significance of Israel in salvation history, and uncritical Christian Zionism, which directly identifies the modern State of Israel with the will of God. Through the concept of the